2022
DOI: 10.1021/acs.est.2c02853
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Collision Cross-Section Values for Extractables and Leachables from Plastic Products

Abstract: The use of ion mobility separation (IMS) in conjunction with high-resolution mass spectrometry has proved to be a reliable and useful technique for the characterization of small molecules from plastic products. Collision cross-section (CCS) values derived from IMS can be used as a structural descriptor to aid compound identification. One limitation of the application of IMS to the identification of chemicals from plastics is the lack of published empirical CCS values. As such, machine learning techniques can p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(43 citation statements)
references
References 69 publications
0
42
0
Order By: Relevance
“…In the CCS prediction model, the CCS values of 93.3% of [M + H] + adducts and 95.0% of [M + Na] + adducts in the test data set were predicted with less than 5% error. 37 Therefore, the tolerance used for the CCS values on screening the measured data against the CPPdb and FCCdb libraries was set to 5%.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the CCS prediction model, the CCS values of 93.3% of [M + H] + adducts and 95.0% of [M + Na] + adducts in the test data set were predicted with less than 5% error. 37 Therefore, the tolerance used for the CCS values on screening the measured data against the CPPdb and FCCdb libraries was set to 5%.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The prediction of CCS values of chemicals associated with plastic products has been described in a previous study, in which the CCS prediction models were built using support vector machine regression (SVM) based on 1076 [M + H] + CCS values and 645 [M + Na] + CCS values. As CCS values are reproducible across different laboratories and platforms, some CCS records for model building were from other publications. ,, …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…p K d and pIC 50 measure the binding affinity of PPARγ, a ligand-activated nuclear receptor involved in multifaceted physiology and chemically induced endocrine disruption . CCS, derived from ion mobility separation (IMS), is a physicochemical property of ions and is related to the chemical structure and three-dimensional conformation of the molecules . FreeSolv provides the experimental hydration free energy of small molecules in water, while Lipo offers experimental results of the octanol/water distribution coefficient (log D at pH 7.4) of 4200 compounds .…”
Section: Materials and Methodsmentioning
confidence: 99%
“…170 Despite the higher prediction error found for some compound classes, according to da Silva et al, it is suggested to use AllCCS as the primary tool for confirmation because it has the highest coverage in CCS prediction compared with other tools and has a perfect Pearson correlation coefficient between experimental and theoretical CCSs. 171 Moreover, it can also provide CCS predictions for small molecules such as drugs, 105 natural products, 172 food contact materials, 155,156 and pesticides. Two clusters contained small molecules, one cluster had lipids associated with it, and the last cluster consisted of carbohydrates and peptides.…”
Section: Metccs and Lipidccsmentioning
confidence: 99%